2017
DOI: 10.1038/ncomms16001
|View full text |Cite
|
Sign up to set email alerts
|

LFA-1 activates focal adhesion kinases FAK1/PYK2 to generate LAT-GRB2-SKAP1 complexes that terminate T-cell conjugate formation

Abstract: Lymphocyte function-associated antigen 1 (LFA-1) affinity and avidity changes have been assumed to mediate adhesion to intercellular adhesion molecule-1 for T-cell conjugation to dendritic cells (DC). Although the T-cell receptor (TCR) and LFA-1 can generate intracellular signals, the immune cell adaptor protein linker for the activation of T cells (LAT) couples the TCR to downstream events. Here, we show that LFA-1 can mediate both adhesion and de-adhesion, dependent on receptor clustering. Although increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 73 publications
(141 reference statements)
3
49
0
Order By: Relevance
“…4D). Additionally, FAK has established roles in T-cell signaling (41,42). Previous reports demonstrated that PI(4,5)P2 binding activated FAK activity (35,43,44).…”
Section: Weak Tcr Signals Activate Fak Via Elevated Pi(45)p2 In Cd4 mentioning
confidence: 99%
“…4D). Additionally, FAK has established roles in T-cell signaling (41,42). Previous reports demonstrated that PI(4,5)P2 binding activated FAK activity (35,43,44).…”
Section: Weak Tcr Signals Activate Fak Via Elevated Pi(45)p2 In Cd4 mentioning
confidence: 99%
“…FAK is basally activated by the Src family kinase LCK in effector T-cells at Y576 or Y577 (depending on species), and Y925. This primes FAK for full activation though phosphorylation at the autophosphorylation site Y397 (herein denoted pY397 FAK) (Chapman and Houtman, 2014), which in turn regulates LFA-1 adhesion and de-adhesion (Raab et al, 2017). Expression of dominant-negative mutants of FAK in T-cells reduces the speed of migration on ICAM-1-coated glass (Rose et al, 2003), and overexpression of a negative regulator of FAK phosphorylation impairs LFA-1 clustering and reduces ICAM-1-LFA-1-driven T-cell homo-aggregation (Giannoni et al, 2003).…”
Section: The Speed Of Actin Retrograde Flow Is Positively Correlated mentioning
confidence: 99%
“…Control of adhesion is achieved through actin linkers (talin and vinculin) and regulatory kinases [FAK (also known as PTK2) and Src family kinases] (Nordenfelt et al, 2016;Raab et al, 2017), a mechanism originally described in other, much more slowly migrating cell types that characteristically form large micron sized focal adhesions (Kanchanawong et al, 2010). These components were originally described in slow migrating adherent cells that characteristically form large micron-sized focal adhesions (Kanchanawong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…FAK is basally activated by Src-family kinase LCK in effector T-cells at Y576/577 and Y925. This primes FAK for full activation at the auto-phosphorylation site pY397 (Chapman & Houtman 2014) which in turn regulates LFA-1 adhesion and deadhesion (Raab et al 2017b). Expression of dominant-negative mutants of FAK in T-cells reduce the speed of migration on ICAM-1 coated glass (Rose et al 2003), and overexpression of a negative regulator of FAK phosphorylation impairs LFA-1 clustering and reduces ICAM-1/LFA-1 driven Tcell homo-aggregation (Giannoni et al 2003).…”
Section: Deleting Ptpn22 Increases T-cell Velocity the Size Of 3d Pymentioning
confidence: 99%
“…Control of adhesion is also achieved through actin linkers (talin, vinculin) and regulatory kinases (FAK, Src family kinases) (Nordenfelt et al 2016;Raab et al 2017a), common to other migrating cell types, that form large micron sized focal adhesions (Kanchanawong et al 2010). In T cells, these complexes are much smaller (nanoscale), containing only a few molecules (Burn et al 2016) but similar in size and composition to nascent adhesions (Changede et al 2015).…”
Section: Introductionmentioning
confidence: 99%